The alphavirus determinants of intercellular long extension formation - Caroline K. Martin; Judy J. Wan; Peiqi Yin; Thomas E. Morrison; William B. Messer; Vanessa Rivera-Amill; Jonathan R. Lai; Nina Grau; Félix A. Rey; Thérèse Couderc; Marc Lecuit; Margaret Kielian (mBio)
ABSTRACT The alphavirus chikungunya virus (CHIKV) is a serious human pathogen that can cause large-scale epidemics characterized by fever and joint pain and often resulting in chronic arthritis. Infection by alphaviruses including CHIKV and the closely related Semliki Forest virus (SFV) can induce the formation of filopodia-like intercellular long extensions (ILEs). ILEs emanate from an infected cell, stably attach to a neighboring cell, and mediate cell-to-cell viral transmission that is resistant to neutralizing antibodies. However, our mechanistic understanding of ILE formation is limited, and the potential contribution of ILEs to CHIKV virulence or human CHIKV infection is unknown. Here, we used well-characterized virus mutants and monoclonal antibodies with known epitopes to dissect the virus requirements for ILE formation. Our results showed that both the viral E2 and E1 envelope proteins were required for ILE formation, while viral proteins 6K and transframe, and cytoplasmic nucleocapsid formation were dispensable. A subset of CHIKV monoclonal antibodies reduced ILE formation by masking specific regions particularly on the E2 A domain. Studies of the viral proteins from different CHIKV strains showed that ILE formation is conserved across the four major CHIKV lineages. Sera from convalescent human CHIKV patients inhibited ILE formation in cell culture, providing the first evidence for ILE inhibitory antibody production during human CHIKV infections.IMPORTANCEChikungunya virus (CHIKV) infections can cause severe fever and long-lasting joint pain in humans. CHIKV is disseminated by mosquitoes and is now found world-wide, including in the Americas, Asia, and Africa. In cultured cells, CHIKV can induce the formation of long intercellular extensions that can transmit virus to another cell. However, our understanding of the formation of extensions and their importance in human CHIKV infection is limited. We here identified viral protein requirements for extension formation. We demonstrated that specific monoclonal antibodies against the virus envelope proteins or sera from human CHIKV patients can inhibit extension formation. Our data highlight the importance of evaluation of extension formation in the context of human CHIKV infection.